Analytical Challenges in Ultra-Trace Quantitation of Nitrosamine Related Impurities within Complex Pharmaceutical Matrices: Review Article (Journal of Pharma Insights and Research, 2025)
The identification of mutagenic N-nitrosamine impurities in widely prescribed pharmaceuticals resulted in a major shift in drug safety assessment and quality control. While initial scrutiny is mostly on the small, volatile dialkyl nitrosamines, the investigation has inevitably expanded to Nitrosamine Drug Substance-Related Impurities (NDSRIs) complex, non-volatile structures formed by the nitrosation of the active pharmaceutical ingredient itself or its synthesis intermediates. Quantifying these impurities at ultra-trace levels, often in the nanogram per day range, presents a formidable analytical obstacle distinct from traditional impurity profiling. NDSRIs frequently lack commercial reference standards, exhibit complex isomeric profiles due to restricted rotation around the N-N bond, and possess physicochemical properties similar to the parent drug, complicating chromatographic separation. Moreover, the pharmaceutical matrix comprising various excipients and high concentrations of the active ingredient introduces significant ion suppression and matrix interference during mass spectrometric detection. A critical, often inevitable risk involves the in-situ formation of artifacts during sample preparation, potentially yielding false positives. This article evaluates the current state of analytical science regarding NDSRIs, focusing on the rigorous demands of sensitivity and selectivity required by regulatory bodies. It details the specific hurdles associated with sample extraction, the necessity of advanced mass spectrometry techniques like LC-HRMS, LC-MS/MS, and Ion Mobility Spectrometry for trace quantification, and the mitigation strategies employed to ensure method robustness. This review discusses about the generic screening methods as well as highly specific, optimized protocols essential for ensuring patient safety.